To kidnap a pope : Napoleon and Pius VII - Caiani, Ambrogio A. (Yale University Press, 2021)
"In the wake of the French Revolution, Napoleon Bonaparte, First Consul of France, and Pope Pius VII shared a common goal: to reconcile the church with the state. But while they were able to work together initially, formalizing an agreement in 1801, relations between them rapidly deteriorated. In 1809, Napoleon ordered the Pope's arrest. Ambrogio Caiani provides a pioneering account of the tempestuous relationship between the emperor and his most unyielding opponent. Drawing on original findings in the Vatican and other European archives, Caiani uncovers the nature of Catholic resistance against Napoleon's empire; charts Napoleon's approach to Papal power; and reveals how the Emperor attempted to subjugate the church to his vision of modernity. Gripping and vivid, this book shows the struggle for supremacy between two great individuals--and sheds new light on the conflict that would shape relations between the Catholic church and the modern state for centuries to come."--